The notions of objectivity and journalistic voice in Arabic language hard news reporting - Alshehri, Abdulmohsin A. (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
A couple of widely-observed and much-discussed related notions within news journalism are